Mechanism of upward mixed crack propagation in long wall working face - CAO Jian; GAO Bin; HUANG Qingxiang (Meikuang Anquan, 2021)
In order to reveal the development mechanism of upward fracture in longwall face mining, based on mixed mode fracture extension theory in fracture mechanics, fracture mechanics is applied to analyze the stress state of strata on the top of the upward fracture, the criterion of upward fracture extension is analyzed, and the development height of upward fracture is determined. Results show that with the working face advances, the development of upward fracture can divided into three stages: generation stage, development and extension stage, and stable stage, and the fracture extension is mixed mode fracture. Based on σ（θ）max theory, the fracture extension theoretical model of upward fracture is established, and the criterion of upward fracture extension is proposed. After full mining, under the action of tensile stress, the crack generated on the top of the rock layer expands downward along the direction of the fracture zone. If it is connected with the upward fracture, the rock layer will be completely broken. Otherwise, if the fracture does not extend and cut-through the strata, the upward fracture does not develop, therefore, the development height of the upward fracture is the distance from top of the seam to the bottom of the strata.